Foreign Direct Investment in Latin America and the Caribbean 2017 - Nations Unies (United Nations, 2017)
This publication sets out and analyses the main foreign direct investment (FDI) trends in the countries of Latin America and the Caribbean. The 2017 edition shows that the region is at a difficult juncture. FDI inflows declined by 7.9% in 2016, to US 167.043 billion, representing a cumulative fall of 17.0% since the peak in 2011. The fall in commodity prices continues to affect investments in natural resources, sluggish economic growth in several countries has slowed the flow of market-seeking capital, and the global backdrop of technological sophistication and expansion of the digital economy has concentrated transnational investments in developed economies.